Numerical analyses of interaction of steel-fibre reinforced concrete slab model with subsoil (Fracture and Structural Integrity, 2016)
Numerical analyses of contact task were made with FEM. The test sample for the task was a steel-fibre reinforced concrete foundation slab model loaded during experimental loading test. Application of inhomogeneous half-space was used in FEM analyses. Results of FEM analyses were also confronted with the values measured during the experiment.
Keywords: Foundation structure; Subsoil–structure interaction; FEM; Steelfibre reinforced concrete